2019
DOI: 10.1111/1911-3846.12495
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Standards Harmonization and Financial Integration

Abstract: We empirically examine whether adopting a uniform set of accounting standards mitigates information frictions in financial markets and facilitates market integration. Using a difference‐in‐difference design, we find that after the mandatory adoption of IFRS local stock returns incorporate more global information and at a faster speed. The effect of IFRS adoption is stronger in countries where there are larger improvements in accounting comparability and for firms with a larger increase in foreign ownership. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 98 publications
(215 reference statements)
1
15
1
2
Order By: Relevance
“…The widespread adoption of IFRS has drawn great interest on investigating the determinants and consequences of adopting IFRS (Zaidi and Huerta, 2014;Zaidi and Paz, 2014;Jung et al, 2016;Houqe, 2018). Researchers find the after-effects of accounting standard harmonization as transparency in accounting statements (Bhat et al, 2016), financial market integration (Dhaliwal et al, 2019), audit efficiency and accuracy (Zhang, 2018) and reduced earnings management (Dayanandan et al, 2016). Thus, a great number of studies explain the nuances of implementing common accounting standards at the firm level (Ipino and Parbonetti, 2017;Onali et al, 2017;Bassemir, 2018;Neel, 2017) and country-level (Juhmani, 2017;Mazzi et al, 2019;Zeng, 2019;Guermazi and Halioui, 2020), but do not explain the spread of IFRS across countries over time.…”
Section: Diffusion Of Ifrs 685mentioning
confidence: 99%
“…The widespread adoption of IFRS has drawn great interest on investigating the determinants and consequences of adopting IFRS (Zaidi and Huerta, 2014;Zaidi and Paz, 2014;Jung et al, 2016;Houqe, 2018). Researchers find the after-effects of accounting standard harmonization as transparency in accounting statements (Bhat et al, 2016), financial market integration (Dhaliwal et al, 2019), audit efficiency and accuracy (Zhang, 2018) and reduced earnings management (Dayanandan et al, 2016). Thus, a great number of studies explain the nuances of implementing common accounting standards at the firm level (Ipino and Parbonetti, 2017;Onali et al, 2017;Bassemir, 2018;Neel, 2017) and country-level (Juhmani, 2017;Mazzi et al, 2019;Zeng, 2019;Guermazi and Halioui, 2020), but do not explain the spread of IFRS across countries over time.…”
Section: Diffusion Of Ifrs 685mentioning
confidence: 99%
“…Esta paridad se podría generar por exigencias del entorno legal, económico, de la industria particular en la que se desenvuelven las empresas o, especialmente, por las necesidades de integración de los mercados de valores (Chumaceiro y Hernández, 2012;young & zeng, 2015;Urdaneta, Pérez y Acurero, 2018;Cantillo y Rivero, 2019;Dhaliwal, He, Li & Pereira, 2019), además, dependería de aspectos como la fortaleza del proceso de emisión y aplicación de las normas contables, el nivel de exigencia de las auditorías independientes, el cumplimiento efectivo de la legislación comercial y el grado de protección de los inversionistas (Archibold et al, 2017;Ross, Shi & Xie, 2019;Cantillo y Rivero, 2019).…”
Section: Marco Conceptualunclassified
“…yDhaliwal et al (2019). Porcentaje de empresas colombianas cotizadas no financieras que revelan sus políticas contables para reconocer sus inventarios en sus estados financieros anuales (2011-2017)…”
unclassified
“…For instance, some scholars found a positive association between IFRS adoption and financial market integration (e.g., Cai & Wong, 2010;E. De George, 2013;Dhaliwal, He, Li, & Pereira, 2019), whereas others found an insignificant association between them (Alnodel, 2016;Naranjo, Saavedra, & Verdi, 2017). Similarly, while some previous studies reported a positive relationship between IFRS and market capitalization (Ben Othman & Kossentini, 2015;Judge et al, 2010;Klibi & Kossentini, 2014;Lasmin, 2011), other studies found a negative link between them (Brochet, Jagolinzer, & Riedl, 2013;Hope et al, 2006;Renders & Gaeremynck, 2007;Shima & Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%